Challenges of Integrating Robotic Surgical Procedures into Graduate Medical Education: State of The Art Review. - Luque Loor, Rosa Johanna; Villegas Villavicencio, Jaira Hailyn; Cherres Bermeo, Jonathan David; Muentes Delgado, Hianny Elian; Cedeño Orejuela, José André; Melis Sosa, Ariel; Añazco Moreira, Paola Ceciliana; Zambrano Zambrano, Gema Paola; Luque Loor, Andy Hermógenes (Spanish Journal of Medical Education, 2026)
Introduction. Robotic surgery is progressively transforming postgraduate medical education (PME); however, its integration into training programs remains heterogeneous, with persistent shortcomings in access, curriculum standardization, resident autonomy, and competency assessment. Objective. To synthesize and map the main challenges associated with integrating robotic surgical procedures into PME across seven domains: access, curriculum, institutional support, resident experience, assessment, barriers, and outcomes. The guiding question was: What are the challenges of integrating robotic surgical procedures into postgraduate medical education? Methods. A narrative thematic review was conducted of peer-reviewed studies published in 2025, in English, and indexed in PubMed, Scopus, and Web of Science. Studies that evaluated the integration of robotic procedures into residency or fellowship programs and addressed at least one of the predefined domains were included. Studies unrelated to GME, technical reports without training outcomes, opinion pieces, preprints, duplicates, and non-robotic training programs were excluded. Ten studies met the inclusion criteria. Data were extracted using a standardized framework, and no meta-analysis was performed. Results: The programs reported unequal access to robotic platforms, dual-console systems, simulators, and protected training time, resulting in fragmented, competency-based curricula with poorly defined milestones and inconsistent institutional support. Although residents showed high motivation, hands-on experience was variable, and autonomy at the console was limited. Available assessment tools showed potential but lacked robust validation and formal alignment with accreditation standards. Implementation was further constrained by high costs, a shortage of trained instructors, medico-legal concerns, workflow limitations, and structural inequalities. The results showed improvements in simulation metrics and processes, while the transfer to independent surgical competence and improved clinical outcomes was inconsistent. Conclusions. The integration of robotic surgery into advanced medical training remains limited by inequities in access and an inconsistent curricular and institutional infrastructure. Its advancement will require standardized, competency-based training pathways, equitable access to technology, and sustained investment in faculty development, simulation, mentorship, and validated assessment systems.